A generic system architecture for simulation based intelligent multi-stage multi-process machining system to achieve zero-defect manufacturing. (2014) - Arif, Muhammad; Xirouchakis, Paul; Bufardi, Ahmed; Akten, Olcay; Nenad, Nesic; Perez, Roberto; Stucki, Michel
No abstract available